Embracing Uncertainty: How literary writing helps us change our minds - Devereux, Kim (Frontiers in Psychology, 2022)
Creative writing and cognitive neuroscience can jointly illuminate how literary writing can change our minds by enhancing our tolerance for uncertainty. From my perspective as a novelist I will show how literary writing hijacks the mechanisms of day-to-day perception and orchestrates cognition to facilitate vividness of (imaginary) experience and insight. Drawing on examples from my novel and other research I will discuss the role of uncertainty and literary devices such as contradiction and paradox in stymieing habitual assumptions whilst inviting the reader’s sensory imagination and conscious awareness, thereby creating an open space for insight. I hypothesize that literary writing promotes a form of dual cognition that involves both sensory experience and detachment, is therapeutic and may share some of the benefits of mindfulness.